Diabetes mellitus, but not small dense low‐density lipoprotein, is predictive of cardiovascular disease: A Korean community‐based prospective cohort study. Issue 6 (15th May 2013) - Suh, Sunghwan; Park, Hyung‐Doo; Jin, Sang‐Man; Kim, Hye Jeong; Bae, Ji Cheol; Park, So Young; Park, Mi Kyoung; Kim, Duk Kyu; Cho, Nam H; Lee, Moon‐Kyu
Abstract Aims/Introduction Small dense low‐density lipoprotein (sdLDL) has been suggested to be a potential risk factor for cardiovascular diseases (CVD). Materials and Methods We carried out a prospective nested case–control study in the Korean Health and Genome Study. Participants were men and women aged 40–69 years who developed CVD (n = 313), and were matched by age and sex to controls who remained free of CVD (n = 313) during the 8‐years follow‐up period (from 2001 to 2009). LDL subfractions were analyzed in frozen samples collected from the 626 participants using polyacrylamide tube gel electrophoresis. Results Patients with CVD had a significantly higher glycated hemoglobin level compared with the controls (5.72 vs 5.56). The proportion of patients with diabetes mellitus (DM) was higher in those who developed CVD during follow up (8.0% vs 1.9%). The frequency of CVD according to each tertile of LDL particle size and the number of metabolic syndrome components did not differ significantly. In the multivariate analysis, DM (odds ratio 4.244, 95% confidence interval 1.693–10.640, P = 0.002) was the only independent predictive factor of CVD. LDL particle size was not associated with the risk for future CVD. Conclusions Small dense LDL might not be a significant predictor of CVD in this Korean community‐based prospective cohort study.